2022
DOI: 10.1007/jhep08(2022)180
|View full text |Cite
|
Sign up to set email alerts
|

Kink-antikink collision in the supersymmetric 𝜙4 model

Abstract: This paper investigates a model containing 𝜙4 kinks interacting with fermions. The fermion back-reaction is included in the equations of motion, which affects the kink-antikink collisions. We show that the fermion field generates a force that can be either attractive or repulsive. Moreover, we investigate three different scenarios, which exhibit a wide variety of behaviors, including the usual scenarios observed in the 𝜙4 model as well as the formation of two oscillons, reflection without contact, one-bounce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 60 publications
1
5
0
Order By: Relevance
“…It is not out of place to mention that kink solitons are special cases of topological solitons [23][24][25]. This has also been indicated in additional works [26,27]. Additionally, dark solitons, that are also known as topological solitons, will be revealed in this work [28].…”
Section: Introductionmentioning
confidence: 56%
“…It is not out of place to mention that kink solitons are special cases of topological solitons [23][24][25]. This has also been indicated in additional works [26,27]. Additionally, dark solitons, that are also known as topological solitons, will be revealed in this work [28].…”
Section: Introductionmentioning
confidence: 56%
“…Recently, the kink-antikink collisions with fermion back-reaction were analyzed for the first time in ref. [58]. It was shown that the interaction could be strongly altered by the back-reaction as well.…”
Section: Jhep12(2022)085mentioning
confidence: 99%
“…For this reason, the fermion can exchange energy with the kink. On the other hand, had we started with a fermion bound only to the kink (or the antikink) at the zero mode, the back-reaction would vanish during the whole evolution of the system [58].…”
Section: Jhep12(2022)085mentioning
confidence: 99%
“…Thus in [23][24][25][26] the transfer of fermions in kink-antikink (or in general, brane collisions) or in kink-impurity was studied, but without back reaction. However, it has only been very recently realized that the back reaction may have a very nontrivial effect on static [28][29][30] as well as on dynamical properties of kinks [31,32]. In particular, in [31], it was shown that the fermion field generates a force, either attractive or repulsive, depending on how one distributes the fermion field on the kink and antikink.…”
Section: Introductionmentioning
confidence: 99%
“…However, it has only been very recently realized that the back reaction may have a very nontrivial effect on static [28][29][30] as well as on dynamical properties of kinks [31,32]. In particular, in [31], it was shown that the fermion field generates a force, either attractive or repulsive, depending on how one distributes the fermion field on the kink and antikink. Thus, resonance windows in the kink-antikink collisions in the supersymmetric φ 4 model could be highly affected by the presence of the fermion.…”
Section: Introductionmentioning
confidence: 99%